Improving the Cu/ZnO-Based Catalysts for Carbon Dioxide Hydrogenation to Methanol, and the Use of Methanol As a Renewable Energy Storage Media - Zhong, Ziyi; Etim, Ubong J.; Song, Yibing (Frontiers in Energy Research, 2020)
Heterogeneous catalytic hydrogenation of CO2 to methanol is a practical approach to mitigating its greenhouse effect in the environment while generating good economic profits. Though applicable on the industrial scale through the syngas route, the catalyst of Cu/ZnO/Al2O3 suffers from a series of technical problems when converting CO2 to methanol directly. They include low single-pass conversion, low methanol selectivity, requiring high pressure and fast deactivation by the reverse water gas shift (RWGS) reaction. Over the years, intensive research efforts have been devoted to proffering solutions to these problems by modifying the existing catalyst or developing new active catalysts. However, the open question is if this type of widely used industrial catalyst still promising for CO2 methanolizing reaction or not? This paper reviews the history of the methanol production in industry, the impact of CO2 emission on the environment, and analyzes the possibility of the Cu/ZnO-based catalysts for the direct hydrogenation of CO2 to methanol. We will not only address the theoretical and technical aspects but also provide insightful views on catalyst development.